OVERCOMING EDUCATIONAL DISRUPTIONS: EFFECTIVE MANAGEMENT TACTICS FOR COVID-19 CHALLENGES - Mubiru, Joseph Kizito; Ssempala , Grace Nalubega (Research Journal of Education and Allied Studies, 2024)
Amidst the unprecedented challenges posed by the COVID-19 pandemic, governments, education systems, and educators worldwide are grappling with the task of ensuring continuity in learning while upholding quality education standards. This paper delves into the multifaceted issues arising from the pandemic's impact on education, addressing questions surrounding the return of students to schools, the potential survival of educational institutions amidst declining enrollments, and the logistical challenges of accommodating increased student numbers while adhering to social distancing measures. Additionally, it explores uncertainties regarding technology adoption among staff and students, considering the existing infrastructure limitations, as well as the financial burdens faced by parents and guardians. Amidst these challenges, institutions are navigating the transition to online blended learning, albeit with concerns about instructor compliance, parental cooperation, and students' accessibility to online classes. By examining these complex dynamics, this paper aims to shed light on the evolving landscape of education in the wake of the COVID-19 pandemic, offering insights into the challenges and opportunities that lie ahead.